2009
DOI: 10.1097/mnm.0b013e32832cc220
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sorafenib treatment in metastatic renal cell carcinoma with 2-fluoro-2-deoxyglucose positron emission tomography and computed tomography

Abstract: An early decrease in the mean glucose uptake was found in both soft and skeletal lesions after treatment with sorafenib. FDG-PET thus seems to be advantageous, compared with RECIST evaluation, which is limited to soft lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 18 publications
2
34
0
1
Order By: Relevance
“…FDG-PET has the advantage, compared with RECIST evaluation, to be not limited to soft lesions; thus, it was possible to detect a decrease in glucose uptake to 82% (53-101%) in skeletal lesions as well [149] . Vercellino et al [150] assessed 11 patients with mRCC who completed at least two cycles of sunitinib and found that early FDG-PET/CT findings, after one cycle of sunitinib, were con- sistent with later CT results in 9 of 11 assessable patients; interestingly, of the other 2 patients that showed a metabolic partial response on PET and stable disease on CT, one achieved a partial response later on, suggesting that metabolic early changes are an indication of sunitinib activity [150] .…”
Section: Antiangiogenetic Therapy Assessmentmentioning
confidence: 98%
See 1 more Smart Citation
“…FDG-PET has the advantage, compared with RECIST evaluation, to be not limited to soft lesions; thus, it was possible to detect a decrease in glucose uptake to 82% (53-101%) in skeletal lesions as well [149] . Vercellino et al [150] assessed 11 patients with mRCC who completed at least two cycles of sunitinib and found that early FDG-PET/CT findings, after one cycle of sunitinib, were con- sistent with later CT results in 9 of 11 assessable patients; interestingly, of the other 2 patients that showed a metabolic partial response on PET and stable disease on CT, one achieved a partial response later on, suggesting that metabolic early changes are an indication of sunitinib activity [150] .…”
Section: Antiangiogenetic Therapy Assessmentmentioning
confidence: 98%
“…Lyrdal et al [149] evaluated the early effects of sorafenib in 10 mRCC patients by using FDG-PET combined with CT. After 1-2 months, the mean glucose uptake in soft lesions decreased to 71% (32-108%); in these lesions the sum of the diameters measured by CT decreased to 80% (57-94%) of the initial value according to RECIST criteria. FDG-PET has the advantage, compared with RECIST evaluation, to be not limited to soft lesions; thus, it was possible to detect a decrease in glucose uptake to 82% (53-101%) in skeletal lesions as well [149] .…”
Section: Antiangiogenetic Therapy Assessmentmentioning
confidence: 99%
“…46 These data are currently limited for mRCC patients, but the technique appears to be promising. 45,47,48 FDG-PET scans reflect changes in the metabolic activity of experimental RCC in preclinical in vivo models that are treated with mTOR inhibitors. 49 Since HIF is regulated by mTOR and given its major effects on glucose metabolism in clear-cell RCC, FDG-PET scans may provide valuable prognostic data for patients treated with mTOR inhibitors or even help select it for second-line targeted agents, which may be used following treatment with tyrosine kinase inhibitors.…”
Section: Diagnostic Implicationsmentioning
confidence: 99%
“…In another trial including 10 patients with 52 metastatic lesions, FDG-PET/CT was performed prior to and 1-2 months after initiation of treatment with sorafenib [52] . It was shown that a significant decrease in glucose uptake was already present in all lesions independent of their location -soft tissue or skeletal system -after 1 month of treatment.…”
Section: Response Assessmentmentioning
confidence: 99%